Regulatory Roles of Sortilin and SorLA in Immune-Related Processes - Talbot, Hugo; Saada, Sofiane; Naves, Thomas; Gallet, Paul-François; Fauchais, Anne-Laure; Jauberteau, Marie-Odile (Frontiers in Pharmacology, 2019)
Sortilin, also known as Neurotensin Receptor-3, and the sorting-related receptor with type-A repeats (SorLA) are both members of the Vps10p domain receptor family. Initially identified in CNS cells, they are expressed in various other cell types where they exert multiple functions. Although mostly studied for its involvement in Alzheimer’s disease, SorLA has recently been shown to be implicated in immune response by regulating IL-6-mediated signaling, as well as driving monocyte migration. Sortilin has been shown to act as a receptor, as a co-receptor and as an intra- and extracellular trafficking regulator. In the last two decades, deregulation of sortilin has been demonstrated to be involved in many human pathophysiologies, including neurodegenerative disorders (Alzheimer and Parkinson diseases), type 2 diabetes and obesity, cancer, and cardiovascular pathologies such as atherosclerosis. Several studies highlighted different functions of sortilin in the immune system, notably in microglia, pro-inflammatory cytokine regulation, phagosome fusion and pathogen clearance. In this review, we will analyze the multiple roles of sortilin and SorLA in the human immune system and how their deregulation may be involved in disease development.